Exploration des liens entre la motivation envers les activités d’orientation et d’information scolaire et professionnelle et l’indécision de carrière des étudiants du collégial - Boulet, Johannie; Guay, Frédéric; Bradet, Richard (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
Research has shown that the more students carry out activities related to their vocational development for pleasure, the less they will be undecided. Thus, intervening to encourage the motivation of college students towards these activities could constitute a way to remedy their career indecision. The aim of this research is therefore to verify whether the motivation to carry out activities promoting vocational development leads to a decrease in the level of indecision of college students. In this longitudinal research conducted with more than 830 students, the results indicate that it is rather the level of indecision that determines the motivation of the students and not vice versa. Thus, the results suggest relying on intervention strategies with regards to student indecision rather than investing in motivational strategies to counter it. Yet, further studies are necessary to better understand this phenomenon among college students. Keywords: motivation, autonomy, career indecision, vocational indecision, young adults, educational and vocational activities, psychological needs